Discourse Battle on Borobudur Temple Tariff Increase Policy in Discourse Analysis Network - Fanny Rosalia (Jurusan Ilmu Komunikasi UTM, 2023)
This study discusses the dynamic process in canceling the Borobudur Temple tariff increase policy using the Discourse Network Analysis (DNA) method and looking at the dynamics that develop through a network of actors and discourses sourced from various online media. The results showed that there was a change in government policy in a short time. The shift of the coalition of supporters to the opposition shows preventive measures in anticipation of widespread chaos. This shows that there are many factors that influence the policy-making process and political decisions. The DNA method used in this study can help map the relationship between actors and discourse in a network, so as to provide a more comprehensive picture of the policy-making process and political decisions. The research also shows the importance of the role of online media in shaping public opinion and influencing the policy-making process. The results of the study showed a change in policy delivered by the government. The shift of the coalition of supporters to the opposition shows preventive measures in anticipation of widespread chaos. In the policy context, this research makes an important contribution in understanding the dynamic processes that occur in policy-making and political decisions, as well as the factors that influence those processes. This can help the government and relevant stakeholders in making better decisions and taking into account all factors involved in policy making